Pengembangan Video Animasi Berbasis Plotagon dan Kinemaster untuk Meningkatkan Hasil Belajar Kognitif Siswa Kelas II SD Islam Lukman Hakim Pakisaji-Malang - Catri Maulidiyah (Jurnal Bidang Pendidikan Dasar, 2022)
The purpose of this study was to determine the feasibility of the media, to determine the readability and attractiveness of the media, to improve students' cognitive learning outcomes by using animated videos based on Plotagon and Kinemaster. The development model used in this research is the ADDIE model. Data analysis used descriptive percentage and N-gain test. The results of the feasibility measurement by material experts reached a percentage of 100% and media experts 88.9%, both of which were stated in the very good category. From students, it was obtained 94.2% for media readability while media attractiveness got 90.7%, each stated in the very good category. There was an increase in the cognitive learning outcomes of class II students, from an average pretest score of 69.67 to an average posttest score of 82.33 with an N-gain value of 0.42 which included a moderate qualification score